Discovery of EST-Derived Microsatellite Primers in the Legume Lens culinaris (Fabaceae) - Neelu Jain; H. K. Dikshit; D. Singh; Akanksha Singh; Harish Kumar (Applications in Plant Sciences, 2013)
Premise of the study: We developed microsatellite markers in the legume Lens culinaris from publicly available databases to enrich the limited marker resource available for the crop. Methods and Results: Eighty-two primer sets were identified using expressed sequence sets of L. culinaris available in the National Center for Biotechnology Information (NCBI) database and were characterized in six species of Lens. Among them, 20 simple sequence repeat (SSR) primers produced no amplification product, 43 produced monomorphic products, and 19 were polymorphic. The primers amplified mono-, di-, tri-, tetra-, penta-, and hexanucleotide repeats with one to four alleles. These SSR loci successfully amplified in five related wild species, with a total of 61 primer pairs in L. nigricans and L. odemensis (98.39%), 59 in L. tomentosus (95.1 %), and 60 in L. ervoides and L. orientalis (96.7%), respectively. Conclusions: The microsatellite markers discovered in this study will be useful in genetic mapping, marker-assisted breeding, and characterization of germplasm.